Recurrent thromboembolism, bleeding, and mortality in Asian patients with venous thromboembolism receiving different oral anticoagulants: A nationwide analysis. Issue 37 (16th September 2022) - Lee, Mei-Chuan; Liao, Chia-Te; Feng, I-Jung; Yu, Tsung; Chang, Wei-Ting; Shih, Mei-Fen; Su, Hui-Chen; Toh, Han Siong
Abstract : Venous thromboembolism (VTE) is associated with a high risk of morbidity and mortality. However, data on the association between oral anticoagulants and the hazards of VTE complications in Taiwanese patients with VTE is limited. This study aimed to compare the hazards of recurrent VTE, bleeding, and mortality between patients with VTE receiving rivaroxaban, a non-vitamin K antagonist oral anticoagulant (NOAC), and those receiving heparin or low-molecular-weight heparin (LMWH) followed by warfarin. Patients with VTE treated with rivaroxaban, or heparin or LMWH followed by warfarin were enrolled from 2 million random samples from Taiwan's National Health Insurance database between 2013 and 2016. Hazards of recurrent VTE (deep vein thrombosis and pulmonary embolism), major bleeding, and mortality in rivaroxaban and warfarin users were investigated. Survival analyses were used to estimate hazard ratios (HRs) and 95% confidence intervals (CIs). Users of rivaroxaban (183) and warfarin (456) were included in the study. Patients receiving rivaroxaban did not have significantly lower hazards of developing recurrent VTE (HR, 0.72 [CI, 0.37–1.37], P  = .31) and mortality (HR, 0.86 [CI, 0.49–1.50], P  = .59) than those receiving heparin or LMWH followed by warfarin. In addition, the hazard ratio of major bleeding was not significantly different between the 2 regimens (HR, 1.80 [CI, 0.39–8.29], P  = .45). Rivaroxaban was not associated with lower risks of recurrent VTE and mortality and higher hazards of major bleeding than heparin or LMWH followed by warfarin in Taiwanese patients with VTE. Clinicians may tailor oral anticoagulants for VTE patients according to the patient's characteristics, cost-effectiveness and healthcare system policy.